Analisis Pemutusan Hubungan Kerja (PHK) pada Pegawai Negeri Sipil (PNS) di Indonesia Definisi, Alasan, Dampak, dan Dasar Hukum - Madaniah, Lilim Halimatul; Supendi, Pepen (CV. Kalimasada Group, 2024)
Termination of Employment (PHK) is a process in which the employment relationship between workers and employers is terminated. Termination of Employment (PHK) is one of the phenomena that often occurs in the world of employment and is an important topic in labor law. Layoffs can be carried out by employers and workers for various reasons, whether caused by economic factors, efficiency, or violations of company regulations. This study aims to analyze the definition, reasons, impact of layoffs and discuss the legal basis and causes of Termination of Employment in Civil Servants (PNS) in Indonesia based on the applicable legal framework. The method used in this research is library research with a qualitative approach with a literature study that includes legislation and previous studies related to layoffs.